Membangun Generasi Emas: Peran Kampus Mengajar dalam Meningkatkan Kualitas Pendidikan Dasar - Hesti Fuji Rastuti; I Made Yoga Arsana Putra; Sadariah; Atika Baiduri (Griya Journal of Mathematics Education and Application, 2025)
Basic education plays a crucial role in shaping a competent generation ready to compete in the global era. However, the quality of basic education in Indonesia still faces challenges, particularly in students' literacy and numeracy skills. The Kampus Mengajar Program, as part of the Merdeka Belajar-Kampus Merdeka (MBKM) policy, aims to address these issues by involving university students as teaching partners in elementary schools, especially in remote areas.This program contributes to improving elementary students' literacy and numeracy skills. Using a descriptive qualitative approach, data was collected through literature reviews and documentation related to the program's implementation at the University of Mataram. The findings indicate that the Kampus Mengajar Program has successfully increased literacy skills by 35% and numeracy skills by 33%. Additionally, the integration of technology in learning further enhances the program’s effectiveness, aligning it with modern educational developments. It is hoped that this success can serve as a reference for policymakers to expand and optimize the Kampus Mengajar Program across Indonesia.